Public perception, practices, and readiness for post Covid-19 lifestyle in Ikolaba Community, Ibadan - Andrew A. Olayemi (Goodwood Publishing, 2020)
Purpose: Besides medical researches that are focused on getting a vaccine, research on the social, economic and cultural implications of the Covid-19 virus are being done. No research has been done to assess the knowledge and practices of the people within a community of a known case of coronavirus in Ibadan metropolis, Nigeria. Therefore, this study assesses the public perception, practices of Covid-19 protocols and readiness for post lockdown. Research methodology: Research design was survey and the method used was interview. 22 respondents participated in the study. Results: The findings indicated that the public perceived the disease as a contagion and a killer. In addition, some did not observe the preventive measures while majority seem cautious. It is recommended that awareness and enlightenment should be intensified especially within the local communities by mobilizing heads of community to commence town halls campaigns. Limitation: Finance was a major limitation because residents wanted to be compensated before participation. Contribution: The implication of this study is that government efforts are impacting the public but more work is needed in the area of educating the public. Keywords: Attitude, Coronavirus, Obstacles, Perception, Readiness